Surface energy effects on the stability of anatase and rutile nanocrystals: A predictive diagram for Nb2O5-doped-TiO2 - da Silva, Andre Luiz; Hotza, Dachamir; Castro, Ricardo H.R. (Applied surface science, 2017)
[Display omitted] •Anatase-rutile phase transition diagram was built for nano Nb2O5-doped-TiO2.•Nb2O5-doping postpones the anatase-to-rutile transition.•The stability crossover for TiO2 was 17.3nm, for 2mol% Nb2O5-doped-TiO2 ∼30nm.•The surface energy for Nb2O5-doped-TiO2 decreases systematically with Nb concentration. Titanium dioxide nanoparticles are widely used for photocatalysis, and the relative fraction of titanium dioxide polymorph, i.e. anatase, rutile, or brookite, significantly affects the final performance. Even though conventional phase diagrams indicate a higher stability for the rutile polymorph, it is well established that nanosizes benefit the anatase phase due to its smaller surface energy. However, doping elements are expected to change this behavior, once changes in both surface and bulk energies may occur. Nb2O5 is commonly added to TiO2 to allow property control. However, the effect of niobium on the relative stability of anatase and rutile phases is not well understood from the thermodynamic point of view. The objective of this work was to build a new predictive nanoscale phase diagram for Nb2O5-doped TiO2. Water adsorption microcalorimetry and high temperature oxide melt solution were used to obtain the surface and bulk enthalpies. The phase diagram obtained shows the stable titania polymorph as a function of the composition and size.